ANALISIS PENGARUH VARIASI ARUS 60A DAN 110A PADA LAS SMAW TERHADAP KEKURANGAN LAS, KERASAN, DAN KEKUATAN BAHAN BESI KARBON ST 60 - Santoso, Budi; ., Titiek Deasy Saptaryani (LENVARI, 2025)
Shielded Metal Arc Welding (SMAW) is widely used in steel construction, where welding current variation strongly affects weld quality, surface defects, and mechanical performance. This study examines the influence of 60A and 110A currents on weld defects, hardness, and impact toughness of ST 60 carbon steel. The methodology includes welding specimens with both current levels, evaluating surface defects using dye penetrant testing, measuring Brinell hardness in the base metal, weld metal, and heat-affected zone (HAZ), and conducting Charpy impact tests. Penetrant results show that 60A produces dominant defects such as excessive spatter and porosity, while 110A generates excessive spatter with one porosity indication. The average weld metal hardness increases from 151.67 HB at 60A to 164 HB at 110A, indicating that higher heat input promotes the formation of a harder microstructure. In contrast, impact toughness decreases from 0.91 J/mm² (60A) to 0.53 J/mm² (110A), demonstrating an inverse relationship between hardness and absorbed energy. Overall, low current triggers porosity due to rapid solidification, whereas high current increases spatter and reduces toughness through microstructural modification. These results emphasize the need for optimal current selection to minimize defects and obtain balanced mechanical properties in ST 60 steel welds